Measuring perceptions of Muslim consumers toward income tax rebate over zakat on income in Malaysia. Issue 2 (5th June 2019) - Al-Mamun, Abdullah-; Haque, Ahasanul; Jan, Muhammad Tahir
Abstract : Purpose: The purpose of this study is to explore the variables that affect Muslim consumers' perception towards tax rebate over zakat on income in Malaysia. Design/methodology/approach: A close-ended structured questionnaire was developed and a total number of 236 valid responses were collected through online survey from the Muslims residing in Malaysia. Findings: This study found that halal-haram aspect of Islamic Shariah, legal consciousness and religiosity of Muslim consumers are positive significant factors for growing perceptions towards tax rebate over zakat on income in Malaysia. Research limitations/implications: This study will definitely play an important leading role for the policy-makers and academicians in understanding the perceptions of Muslim consumers. Practical implications: This study can assist zakat and tax authorities in Malaysia for taking corrective actions to adapt or improve the current policy on the basis of its Muslim consumers' perception. Social implications: The findings of this study can reduce the gap of understanding among Muslims in the society by letting other people's perceptions towards tax rebate through zakat system in Malaysia. Originality/value: As there are not enough studies in this area, this study will definitely play an important leading role for the countries or policy-makers or concerned zakat or tax institutions all over the world in capitalizing the practices which is highly and positively perceived by the Muslim consumers in Malaysia.